Prehospital Buprenorphine Treatment for Opioid Use Disorder by Paramedics: First Year Results of the EMS Buprenorphine Use Pilot. (3rd April 2023) - Hern, H. Gene; Lara, Vanessa; Goldstein, David; Kalmin, M.; Kidane, S.; Shoptaw, S.; Tzvieli, Ori; Herring, Andrew A.
Abstract: Background: Prehospital initiation of buprenorphine treatment for Opioid Use Disorder (OUD) by paramedics is an emerging potential intervention to reach patients at greatest risk for opioid-related death. Emergency medical services (EMS) patients who are at high risk for overdose deaths may never engage in treatment as they frequently refuse transport to the hospital after naloxone reversal. The potentially important role of EMS as the initiator for medication for opioid use disorder (MOUD) in the most high-risk patients has not been well described. Setting: This project relies on four interventions: a public access naloxone distribution program, an electronic trigger and data sharing program, an "Overdose Receiving Center, " and a paramedic-initiated buprenorphine treatment. For the final intervention, paramedics followed a protocol-based pilot that had an EMS physician consultation prior to administration. Results: There were 36 patients enrolled in the trial study in the first year who received buprenorphine. Of those patients receiving buprenorphine, only one patient signed out against medical advice on scene. All other patients were transported to an emergency department and their clinical outcome and 7 and 30 day follow ups were determined by the substance use navigator (SUN). Thirty-six of 36 patients had follow up data obtained in the short term and none experienced any precipitated withdrawal or other adverse outcomes. Patients had a 50% (18/36) rate of treatment retention at 7 days and 36% (14/36) were in treatment at 30 days. Conclusion: In this small pilot project, paramedic-initiated buprenorphine in the setting of data sharing and linkage with treatment appears to be a safe intervention with a high rate of ongoing outpatient treatment for risk of fatal opioid overdoses.